2022
DOI: 10.3390/buildings12050559
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Exterior Quality of Traditional Residences: A Genetic Algorithm–Backpropagation Approach

Abstract: The visual aesthetics of villages are remarkably affected by the exterior quality of traditional residences, influencing the impression and assessment of local culture. A proper scientific assessment of exterior quality can protect traditional cultures and improve the development of villages. This research was conducted in a village consisting of 115 residences (Mengjinglai village, which is on the border between China and Myanmar). The backpropagation (BP) neural network model with genetic algorithm (GA) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Although this study adopted rigorous data processing and statistical analysis methods to improve the reliability of the research results, it should be noted that the use of a GA-BP neural network for landscape quality assessment is a relatively new method, and its effectiveness in different contexts remains to be further investigated. Future research could compare the results of this method with traditional methods to evaluate its reliability and validity (Xu et al, 2022;Jiao et al,2023).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study adopted rigorous data processing and statistical analysis methods to improve the reliability of the research results, it should be noted that the use of a GA-BP neural network for landscape quality assessment is a relatively new method, and its effectiveness in different contexts remains to be further investigated. Future research could compare the results of this method with traditional methods to evaluate its reliability and validity (Xu et al, 2022;Jiao et al,2023).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of morphological indica models to study the spatial morphology of traditional villages has emerged as a new search field. The application of new technologies and methods is increasing, includ Space Syntax [26,27], machine learning [28,29], BIM technology [30,31], SD (system namics) technology [32,33], and CA (cellular automaton) technology [34,35]. Th…”
Section: Analysis Of Village Morphology Indicatorsmentioning
confidence: 99%
“…In recent years, the use of morphological indicator models to study the spatial morphology of traditional villages has emerged as a new research field. The application of new technologies and methods is increasing, including Space Syntax [26,27], machine learning [28,29], BIM technology [30,31], SD (system dynamics) technology [32,33], and CA (cellular automaton) technology [34,35]. These methods are applied in the fields of static and dynamic quantitative calculations for analyzing the spatial morphology of traditional villages [36], as well as their driving factors [37,38], and for simulating planning scenarios [39].…”
Section: Analysis Of Village Morphology Indicatorsmentioning
confidence: 99%
“…Ciesielski et al [13] found images with high aesthetic value using feature extraction methods from machine learning based on two image databases rated by humans. A number of research studies, referenced as [14][15][16][17][18][19], have been carried out concerning machine learning in relation to free-form surface structures. Some of these articles have emphasized aesthetics as their main area of interest.…”
Section: Introductionmentioning
confidence: 99%